Self-concern : an experiential approach to what matters in survival - Martin, Raymond (Cambridge : Cambridge University Press, 2008)
This text makes a significant contribution to the philosophical literature on the nature of the self, personal identity, and survival.
1. Questions; 2. Anticipation; 3. Rejuvenation; 4. Transformation; 5. Identification; 6. Experience
Includes bibliographical references and index.
Keywords: Self (Philosophy).; Identity (Psychology).; Future life